2020
DOI: 10.1002/bab.2021
|View full text |Cite
|
Sign up to set email alerts
|

The effects of high‐fat diet and metformin on urinary metabolites in diabetes and prediabetes rat models

Abstract: High-fat diet (HFD) interferes with the dietary plan of patients with type 2 diabetes mellitus (T2DM). However, many diabetes patients consume food with higher fat content for a better taste bud experience. In this study, we examined the effect of HFD on rats at the early onset of diabetes and prediabetes by supplementing their feed with palm olein oil to provide a fat content representing 39% of total calorie intake. Urinary profile generated from liquid chromatography-mass spectrometry analysis was used to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Of relevance to the present study are other published works where multivariate data analyses have been used to improve our understanding of the differences between various rodent metabolic models, for example, by characterising the different metabolic profiles of lean, high-fat diet (HFD)-fed and HFD/streptozotocin (STZ)-induced T2D rats ( Chen et al, 2021 ) or of HFD/STZ-induced T2D vs. STZ-induced type I diabetic rats ( Mediani et al, 2018 ). The impact of diabetic status on the metabolic response to HFD has also been explored using this methodology ( Lee et al, 2021 ). In addition, Letsinger et al (2020) demonstrated how a high-fat/high-sugar diet differentially affects the gut metabolome between male and female mice, which is of particular importance given the predominance of male rodent use in animal dietary studies and the lack of studies comparing the responses of male and female rodents to obesogenic feeding, as identified in our literature survey.…”
Section: Discussionmentioning
confidence: 99%
“…Of relevance to the present study are other published works where multivariate data analyses have been used to improve our understanding of the differences between various rodent metabolic models, for example, by characterising the different metabolic profiles of lean, high-fat diet (HFD)-fed and HFD/streptozotocin (STZ)-induced T2D rats ( Chen et al, 2021 ) or of HFD/STZ-induced T2D vs. STZ-induced type I diabetic rats ( Mediani et al, 2018 ). The impact of diabetic status on the metabolic response to HFD has also been explored using this methodology ( Lee et al, 2021 ). In addition, Letsinger et al (2020) demonstrated how a high-fat/high-sugar diet differentially affects the gut metabolome between male and female mice, which is of particular importance given the predominance of male rodent use in animal dietary studies and the lack of studies comparing the responses of male and female rodents to obesogenic feeding, as identified in our literature survey.…”
Section: Discussionmentioning
confidence: 99%
“…Mediani et al [ 82 ] performed NMR-based untargeted metabolomic analysis to understand the biochemical changes in streptozotocin (STZ)-induced, normal-, and obese-diabetic rates with metformin treatment (150 mg/kg/day), suggesting that metformin may provide better improvement for T2DM complications and insulin sensitivity for obese diabetes rather than normal diabetes. Lee et al [ 83 ] also carried out an LC-MS-based untargeted urinary metabolomics study in diabetes and prediabetes rat models, revealing the alteration of urine metabolomes. For prediabetic rats, metformin treatment (250 mg/kg/day) altered the urinary metabolite profile to be more like that of healthy rats ( Table 3 ).…”
Section: Urinary Metabolome and Metformin Treatmentmentioning
confidence: 99%
“…Therefore, the use of STZ + HFD has been reported to impair the secretions of insulin, which causes hyperglycemia and dyslipidemia, amongst other disorders [ 42 , 43 , 44 ]. Our study showed significant increases in blood glucose on the third day of STZ injection in rats fed with HFD.…”
Section: Discussionmentioning
confidence: 99%